2018
DOI: 10.1002/syn.22042
|View full text |Cite
|
Sign up to set email alerts
|

Kappa opioid receptor binding in major depression: A pilot study

Abstract: Endogenous kappa opioids mediate pathological responses to stress in animal models. However, the relationship of the kappa opioid receptor (KOR) to life stress and to psychopathology in humans is not well described. This pilot study sought, for the first time, to quantify KOR in major depressive disorder (MDD) in vivo in humans using positron emission tomography (PET). KOR binding was quantified in vivo by PET imaging with the [ C]GR103545 radiotracer in 13 healthy volunteers and 10 participants with current M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
3
12
1
1
Order By: Relevance
“…The overall conclusion from animal models supports the idea that the KOR system may underpin aspects of sadness and dysphoria but that the cause of the opioid alterations in MDD remains inconclusive (28). Nevertheless, in a pilot study, no differences in KOR binding (using [11C]GR103545) could be found between MDD patients and controls (29), while prodynorphin mRNA was significantly lower in MDD and bipolar depression as compared with controls (30).…”
Section: Introductionsupporting
confidence: 55%
“…The overall conclusion from animal models supports the idea that the KOR system may underpin aspects of sadness and dysphoria but that the cause of the opioid alterations in MDD remains inconclusive (28). Nevertheless, in a pilot study, no differences in KOR binding (using [11C]GR103545) could be found between MDD patients and controls (29), while prodynorphin mRNA was significantly lower in MDD and bipolar depression as compared with controls (30).…”
Section: Introductionsupporting
confidence: 55%
“…This kind of sad reflection provoked greater increases in [ 11 C]Caf ( 8 ) binding in widespread brain regions of women with major depression [189], suggesting an exaggerated opioid response in relation to mood disorder, as distinct from ordinary sadness. A pilot PET study with the κOR-ligand [ 11 C]GR103545 ( 25 ) did not reveal any binding differences between healthy control and patients suffering from major depression [190]. However, a [ 11 C]EKAP ( 27 ) κOR study in healthy volunteers showed an inverse correlation between social status and [ 11 C]salvinorin A ( 33 ) binding in widespread brain areas, with a special association occurring in brain regions mediating reward or aversion [191].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The first-in-man study was performed in Naganawa et al (2014) and showed the suitability of the tracer for imaging and quantifying kappa receptors in humans, although quantification of kinetic parameters can be difficult due to lack of a reference region and to slow kinetics. Recently, a pilot study of kappa opioid receptor binding in major depression was conducted, using [ 11 C]GR103545 to compare distribution volumes between healthy volunteers and patients suffering from major depressive disorder; no significant differences were detected (Miller et al, 2018). The tracer was also used to investigate the effect of various ligands on the kappa opioid receptor in rodents (Placzek et al, 2015).…”
Section: State Of the Art Of Existing Pet Agonist Radiotracers For Nementioning
confidence: 99%